Novice teachers' pedagogical content knowledge for planning and implementing mathematics and science lessons. (July 2022) - Amador, Julie M.; Rogers, Meredith A. Park; Hudson, Rick; Phillips, Andrea; Carter, Ingrid; Galindo, Enrique; Akerson, Valarie L.
Abstract: To understand novice teachers' pedagogical content knowledge, this study focuses on first-year teachers' planning and implementation of lessons incorporating students' representations, the exposure and sharing of students' ideas, and assessment. We examined 11 teachers' plans and implementation of two mathematics and two science lessons. Data included lesson plans, field notes, classroom observation protocols, and interviews. We found (a) teachers' planning for use of representations was similar for mathematics and science, (b) high levels of exposing and sharing students' thinking in science and mathematics lessons, and (c) diverse assessment practices, with assessment occurring more often in mathematics lessons than science lessons. Highlights: Minimal difference in how teachers planned for and used representations in science and mathematics lessons. Many teachers had high levels of exposure and sharing in both science and mathematics lessons. Teachers' assessment practices ranged during lessons and from one lesson to the next. Comparing representations, expose/share, and assessment between content areas, greatest differences were in assessment. Teachers included representations, exposure/sharing, and assessment in lesson implementation not included in planning.